1975
DOI: 10.1104/pp.56.6.731
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Abscisic Acid Levels in Germinating and Nongerminating Lettuce Seed

Abstract: The concentrations of abscisic acid in Grand Rapids lettuce (Lactuca sativa L.) seeds imbibed under conditions which promote or inhibit germination were determined by electron capture-gas chromatography. The concentration of abscisic acid in dry seeds was 12 to 14 nanograms per 100 milligrams. During 24-hour imbibition, the abscisic acid content diminished more rapidly during conditions which allow germination (25 C in (3,11,12,18). Similarities in the effects of high temperature (35 C) and ABA and their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…Our results, while not contradictory to, do not wholly agree with those of Braun and Khan (1975) and Poggi‐Pellegrin and Bulard (1976) who used the cultivar Grand Rapids, and are not in complete agreement with Aspinall et al (1967) who used Great Lakes. We have found that either GA or cytokinin alone can overcome ABA induced inhibition of germination.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results, while not contradictory to, do not wholly agree with those of Braun and Khan (1975) and Poggi‐Pellegrin and Bulard (1976) who used the cultivar Grand Rapids, and are not in complete agreement with Aspinall et al (1967) who used Great Lakes. We have found that either GA or cytokinin alone can overcome ABA induced inhibition of germination.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies on barley (Wang et al. , 1995), wheat (Ried and Walker‐Simmons, 1990), lettuce (Braun and Khan, 1975) and tobacco (Grappin et al. , 2000) have also all found higher ABA levels in imbibed D grains/seeds than in ND grains/seeds.…”
Section: Discussionmentioning
confidence: 83%
“…The data collected so far do not give an unambiguous confirmation of that assumption. In some cases the light stimulus causes a rapid increase 0 f hormone level (GA4 in apple embryos, Smolenska and Lewak, 1971, GA9 in lettuce seeds, Bianco and Bulard, 1981), but in other cases changes in the content of hormones arc not observed (ABA in lettuce seeds, Khan and Braun, 1975;GA4 and GA7 in the same material; Bianco and Bulard, 1981). Similarly, chilling of imbibed apple or sugar mapple seeds results in pronounced rise in GAs and CKs levels.…”
Section: Environmental Control Of the Dormancy Removal And Germinationmentioning
confidence: 94%